2012
DOI: 10.1038/onc.2012.154
|View full text |Cite
|
Sign up to set email alerts
|

Met signaling regulates growth, repopulating potential and basal cell-fate commitment of mammary luminal progenitors: implications for basal-like breast cancer

Abstract: Basal-like breast cancer is an aggressive subtype of mammary carcinoma. Despite expressing basal markers, typical of mammary stem cells, this tumor has been proposed to originate from luminal progenitors, which are downstream of stem cells along the mammary epithelial hierarchy. This suggests that committed luminal progenitors may reacquire basal, stem-like characteristics, but the mechanisms that regulate this transition remain unclear. Using mouse models, we found that luminal progenitors express high levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 59 publications
5
57
0
Order By: Relevance
“…24 Constitutively stimulated MET increases clonogenic growth and enables the reconstitution of mammary glands, and MET-activated progenitors also direct cell fate toward the basal lineage. 25 Therefore, MET may play a crucial role in the development of TNBC and thus could be a potential therapeutic target.…”
mentioning
confidence: 99%
“…24 Constitutively stimulated MET increases clonogenic growth and enables the reconstitution of mammary glands, and MET-activated progenitors also direct cell fate toward the basal lineage. 25 Therefore, MET may play a crucial role in the development of TNBC and thus could be a potential therapeutic target.…”
mentioning
confidence: 99%
“…Some adult mouse mammary progenitors assumed to be luminally-restricted, can be stimulated to differentiate into multiple lineages after being “passaged” in vivo under the kidney capsule in collagen or in collagen/Matrigel gels [7]. It has also been found that adult basal and luminal cells exhibit increased potential to repopulate a mammary gland following constitutive Met activation [84], or after transient co-expression of Slug and Sox9 [79], or expansion in vitro in the presence of Matrigel and fibroblast feeders [47]. Interestingly, the frequency of fetal and adult cells that can produce MRUs in this latter type of Matrigel culture is >20-fold and >100-fold greater, respectively, than the frequency of MRUs detectable in the cells used to initiate the cultures.…”
Section: Variable Control and Expression Of The Mammary Stem Cell Statementioning
confidence: 99%
“…Interestingly, it has been shown that, in oval cells expanded in vitro, MET and EGFR sustain selfrenewal and binary cell fate decision, promoting respectively hepatocyte or cholangiocyte commitment through alternative signaling pathway: MET via AKT and STAT3, EGFR via Notch [61]. A recent study on the mouse mammary epithelium revealed that MET is specifically expressed in luminal progenitors, and showed that HGF retains cells in the stem/progenitor state, preventing differentiation toward the mature luminal phenotype [62]. Interestingly, this may have pathogenetic implications for human basal-like breast cancer that likely derives from transformation of luminal progenitors [63], retains stem-like features, and express significant levels of wild-type MET [64].…”
Section: Met Regulates Normal and Cancer Stem Cell Phenotypes: 'Inhermentioning
confidence: 97%